2021
DOI: 10.3389/fcvm.2021.690240
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Left and Right Atrial Strains Using Cardiovascular Magnetic Resonance Based Tissue Tracking

Abstract: Background: Left and right atrium (LA and RA) exert an essential and dynamic role in ventricular filling and hence affect heart performance. Strain quantification has been reported as a novel parameter to assess function. However, the assessment of bi-atrial strains with cardiovascular magnetic resonance (CMR) based techniques is still limited and gender- and age-specific normal values in a healthy population are missing.Methods: One hundred and fifty healthy volunteers (49.8 ± 17.3 years, 75 males) undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
(48 reference statements)
3
16
0
Order By: Relevance
“…Whereas some studies claim that there is a correlation between the heart rate and aggravation in atrial contraction, some other studies refute this notion (27,46). According to our results, an increase in age was correlated with an increase in the RA contraction function; be that as it may, this association cannot be considered etiologic because what we sought to determine was the source of heterogeneity between studies.…”
Section: Ra Stementioning
confidence: 46%
“…Whereas some studies claim that there is a correlation between the heart rate and aggravation in atrial contraction, some other studies refute this notion (27,46). According to our results, an increase in age was correlated with an increase in the RA contraction function; be that as it may, this association cannot be considered etiologic because what we sought to determine was the source of heterogeneity between studies.…”
Section: Ra Stementioning
confidence: 46%
“…Of the clinical covariates, male sex, atrial fibrillation, and a NYHA class of > II were univariable predictors of all-cause mortality ( Table 4 ). Since previous research showed that RA and RV strain values differ between males and females ( 18 ), a sub-analysis was performed to evaluate whether the correlation of RA strain with all-cause mortality differed between the sexes. In female patients ( n = 58), RA reservoir and conduit strain were predictors of all-cause mortality ( n = 9, data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Further work to evaluate AI metrics in risk stratification is required as has been achieved for RV measurements [ 33 ]. In addition further work will be to clinically evaluate the range of physiological parameters that can be extracted from the AI segmentations, such as RA strain [ 36 , 37 ] and potentially reservoir and conduit function [ 38 , 39 ]. RHC measurements correlated strongly with AI RA measurements, indicating AI metrics may provide physiologically accurate measure of pathophysiological changes in the heart given their high consistency and repeatability.…”
Section: Discussionmentioning
confidence: 99%